PELAYANAN KESEHATAN VIRTUAL PADA PASIEN GAGAL JANTUNG SELAMA PANDEMI COVID-19; SEBUAH TINJAUAN LITERATUR - bambang aditya nugraha (Unit Penelitian dan Pengabdian Kepada Masyarakat, STIKES Dirgahayu Samarinda, 2020)
ABSTRACT Heart failure is a chronic disease whose therapeutic regimen must be carried out continuously in order to maintain circulation and minimize deterioration. The covid-19 pandemic has prevented heart failure patients from getting health services directly. Remote or virtual health services can be carried out for patients with heart failure in order to prevent the spread and transmission of Covid 19 and maintain quality of life. The purpose of this literature is to explain that health care for patients with heart failure can be done virtually. The research method used is narrative review using Google Scholar and pubmed as the database of articles. Article inclusion criteria are published during the COVID-19 pandemic, in Indonesian and in English, and a complete manuscript is available. The keywords used virtual care and heart failure and covid-19. The search results showed 1392 articles, but only 5 articles that matched the predetermined criteria and it was found that virtual health services for heart failure patients were recommended to be carried out in order to meet patient needs and prevent the spread and transmission of covid 19. The search results were expected to become information related to alternative health services for patients with heart failure during the pandemic and improve quality of life. Key Words — care, covid-19, heart failure, virtual health service